SURVEY OF FABRIC RE-DYEING ACTIVITIES AS A POTENTIAL ENVIRONMENTAL PROBLEM IN URBAN KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
A new re-dyeing practice has emerged and is fast spreading in urban Kano causing damage to the environment. This survey was carried out to assess selected fabric re-dyeing activity sites and their environmental impacts. This was achieved with the aid of designed questionnaire. Nine major dyeing sites in urban Kano: Kofar Mata, Chiranci, Karshen Waya, Rijiyar Zaki, Jan Bulo, Zawaciki, Kofar Na’isa, Karofin Zage and Goron Dutse dyeing pits were surveyed. The result revealed that individuals involved are males within the age range of 14 – 35years. The major sources of water are; pipe borne water, earthen dug wells and motorized borehole pumps. The dye wastewater is usually discharged untreated into street drains, ground surface and constructed pits. Individuals involved use protective measures such as face masks, hand gloves and traditional leather jackets. The dye powders, solutions and other constituents, when in contact with the skin cause serious burns, skin hardening and irritations. Inhalation of the gas emitted by the dye solution causes stomach upset and swelling of the body, which may sometimes be treated traditionally. The dye wastewater also destructs plantations/vegetation and inhibits survival of soil invertebrates such as earthworms. This calls for a general enlightenment to the users and general public on both the environmental and health risks of these substances
Keywords: Dyeing, dyes, environmental impact, protective measures, wastewater